Atenção e vigilância em saúde: sínteses de evidências e análise espacial múltipla - Donida, Giovana (Universidade Federal de São Carlos, 2024)
Syphilis is a public health problem in Brazil and around the world, which disproportionately affects marginalized and vulnerable groups. Objective: To synthesize knowledge about health care and surveillance for syphilis, and identify areas of multiple occurrence of the disease in subpopulations. Methods: This is a combined study that encompasses several methods simultaneously, initiated by a systematic scoping review with the aim of mapping the scientific evidence regarding the treatment of the partner of pregnant women diagnosed with syphilis, an integrative review to identify the scientific productions that use spatial and/or spatio-temporal analysis technologies for the distribution of syphilis cases, and finally, an epidemiological, non-experimental, ecological, retrospective study with multiple group design to characterize the occurrence of syphilis cases acquired, pregnant and congenital, and identify the spatial clusters, in the 645 municipalities of the state of São Paulo in the period 2018 – 2022. Usually review studies do not involve the aspects established by Resolution nº 466, of December 12, 2012; as well as meeting the ethical specificities of research of strategic interest to the SUS, established in Resolution No. 580, of March 22, 2018. Results and Discussion: In the systematic scoping review, it was possible to identify the factors that act to prevent treatment of the pregnant woman's partner with syphilis: difficulty in accessing health services, working hours incompatible with the functioning of health services, inability to include the partner in prenatal care, lack of guidelines and public policies including the partner and health of men, social and economic vulnerability, lack of knowledge and stigma about the disease on the part of the pregnant woman and her partner. In the integrative review, it was possible to identify the profile and behavior of syphilis, the clusters that correlate with socio-spatial markers and epidemiological profiles, characterized by high population density, inadequate prenatal care, population migration to developed and/or developing areas. In the ecological study, 14 municipalities were identified with a high Relative Risk (RR) for the occurrence of acquired, pregnant and congenital syphilis, of which 14.3% were according to the São Paulo Social Responsibility Index (IPRS), as municipalities vulnerable. Conclusion: The research findings allow us to affirm that syphilis health care and surveillance, considering the subpopulations, require implementations articulated with the partnership's expanded prenatal practice, use of spatial and spatio-temporal analysis tools to improve health surveillance actions and intensify priority interventions for municipalities at high risk for multiple, bi- and univariate occurrences of acquired syphilis, in pregnant women and congenital.
Health care and surveillance: evidence synthesis and multiple spatial analysis
Keywords: Sífilis; Evidências em saúde; Análise espacial; Análise espaço-temporal; Parceiro; Syphilis; Health evidence; Spatial analysis; Spatio-temporal analysis; Partnership; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA